DYNAMICS OF MARRIAGE DISPENSATION IN PANGKALAN BUN: IMPLICATIONS FOR CHILDREN’S RIGHTS AND PROTECTION - Said Romadhon, Ahmad; Khair, Abdul; Murtadho, Ali; Andleeb, Naima (EMPOWERING HUMANITY, 2025)
Dispensation of marriage is one of the issues that often becomes a concern in the context of child protection in Indonesia, including in West Kotawaringin Regency, especially in Pangkalan Bun. This study analyzes the dynamics of marriage dispensation in Pangkalan Bun and its implications for children’s rights and protection. The research method used a qualitative approach with primary data obtained through in-depth interviews with religious courts, child protection organizations, community leaders, and families who applied for marriage dispensation. The results showed that marriage dispensation is often used due to economic factors, pregnancy outside marriage, and social pressure. However, this practice has the potential to violate children’s rights, such as the right to education, health, and protection from exploitation. This article recommends strengthening regulations, improving community education, and improving access to child protection services to reduce the negative impact of marriage dispensation.